2021
DOI: 10.3346/jkms.2021.36.e319
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) Scale for Assessing Work-related Stress and Anxiety in Healthcare Workers in Response to Viral Epidemics

Abstract: Background The coronavirus disease 2019, or COVID-19, has had a major psychological impact on healthcare workers. However, very few scales are available to specifically assess work-related stress and anxiety in healthcare workers responding to a viral epidemic. This study developed a new assessment tool, the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) and aimed to validate it among healthcare workers directly affected by COVID-19 in Korea. Methods A total of 1,019 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 26 publications
2
90
0
8
Order By: Relevance
“…In this study, the mean score of SAVE-9 was 23.0. Considering that our previous study describing the SAVE-9 proposed a cut-off score of 22 points ( 44 ), we observed that 241 (62%) of healthcare workers showed work-related stress and anxiety during the pandemic. This finding is consistent with previous studies confirming a substantial proportion of mental health issues among healthcare workers ( 12 , 13 , 16 , 51 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, the mean score of SAVE-9 was 23.0. Considering that our previous study describing the SAVE-9 proposed a cut-off score of 22 points ( 44 ), we observed that 241 (62%) of healthcare workers showed work-related stress and anxiety during the pandemic. This finding is consistent with previous studies confirming a substantial proportion of mental health issues among healthcare workers ( 12 , 13 , 16 , 51 ).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, early detection, screening, and interventions are crucial. The SAVE-9 is a virus-related anxiety and work stress scale developed by Chung ( 44 ) to directly reflect the psychological stress in relation to the viral epidemic during COVID-19. Traditional assessment scales such as the Generalized Anxiety Disorder-seven items (GAD-7) ( 45 ), Zung's Self-rating Anxiety Scale (SAS) ( 46 ), and the Depression Anxiety and Stress Scale ( 47 ) are general scales to evaluate the anxiety of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…The SAVE-6 scale is a self-reporting rating scale which was developed to measure the respondent's anxiety response to the COVID-19 pandemic ( 28 ). It was derived from the original SAVE-9 scale, in order to measure the work-related stress and anxiety of healthcare workers in response to the COVID-19 pandemic ( 29 ). The SAVE-6 scale was validated among the general population in various languages, including Korean ( 28 ), Arabic ( 30 ), and English ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, specifically assessing healthcare workers' anxiety responses to the viral epidemic to manage their mental health should be considered important. For that, Chung et al (11) developed the Stress and Anxiety to Viral Epidemics-9 items (SAVE-9) scale to measure healthcare workers' work-related stress and anxiety responses during the pandemic. It is a 9item self-rating scale and validated in Korean (11), Russian (12), Italian (13), Japanese (14), Turkish (15), and German (16).…”
Section: Introductionmentioning
confidence: 99%
“…For that, Chung et al (11) developed the Stress and Anxiety to Viral Epidemics-9 items (SAVE-9) scale to measure healthcare workers' work-related stress and anxiety responses during the pandemic. It is a 9item self-rating scale and validated in Korean (11), Russian (12), Italian (13), Japanese (14), Turkish (15), and German (16). The SAVE-6 scale, derived from the SAVE-9 scale, used to assess the anxiety response of the general population, was validated in Korean (17), Lebanese (18), and American samples (19).…”
Section: Introductionmentioning
confidence: 99%